Coating diaphragm as well as preparation method and application thereof
By using a coated separator in a lithium metal battery, the separator contains lithium salts, oxides and binders, it solves the instability of the electrode interface of the lithium metal battery under high voltage, and achieves higher electrochemical performance and longer cycle life.
Patent Information
- Application Number
- CN202510007974.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-18
AI Technical Summary
When lithium metal batteries are used at high voltages, the instability of the electrode interface leads to dendrite growth and the instability of the solid electrolyte interface (SEI), affecting the cycle life and performance of the battery.
A coating membrane is used, which consists of a base membrane, a coating and a binder, the coating containing a lithium salt, an oxide and a binder, wherein the lithium salt includes a nitrogen-containing lithium salt, an oxide includes silicon oxide, and the binder is polyvinylidene fluoride. This coated separator is suitable for high-voltage lithium metal batteries by inhibiting dendrites and promoting the stability of SEI.
By inhibiting dendrite growth and promoting SEI stability, the coated separator significantly improves the electrochemical performance and safety of lithium metal batteries and extends the cycle life of the battery.
Smart Images

Figure CN119852640A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a coating diaphragm, a preparation method thereof and applications thereof. Background Art
[0002] The continuous development of energy storage technology is key to meeting the growing demands of modern electronic devices, electric vehicles, and renewable energy systems. Among various battery technologies, lithium metal batteries are highly regarded for their superior energy density, providing a promising path to achieve longer-lasting and more efficient power sources. Despite their potential, the practical application of lithium metal batteries still faces huge challenges, mainly related to dendrite formation, the stability of the solid electrolyte interface (SEI), and maintaining long-term stable cycle performance. In addition, when lithium metal batteries operate at high voltages above 4V, the decomposition and consumption of the electrolyte is more intense, which greatly aggravates the instability of the electrode interface. Therefore, improving the stability of the electrode interface of lithium metal batteries is crucial to improving the cycle life and performance of lithium metal batteries.
[0003] In the composition of lithium metal batteries, a key component is the separator, which is essential as a physical barrier to prevent direct contact between the negative and positive electrodes while allowing ion transport. The integrity of the separator is critical to ensure the safety and operational stability of the battery. However, traditional separators have shown limitations in effectively solving the complex challenges associated with lithium metal batteries, especially in mitigating dendrite growth and ensuring the formation of a stable and durable SEI layer. These shortcomings highlight the urgent need for innovative separator technologies.
[0004] Improving the separator structure or surface modification coating is considered an important means to improve separator performance. The conceptualization of this advanced separator technology marks a major step forward in overcoming the limitations of current high-voltage lithium metal battery design. By focusing on the role of separators in improving battery safety and efficiency, it will help promote the wider popularization of lithium-based energy storage. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a coated diaphragm, a preparation method and application thereof. The coated diaphragm provided by the present invention can inhibit dendrite growth and promote SEI stability while being compatible with the stable operation of the high-voltage positive electrode, and can prepare a high-stability high-voltage lithium metal battery.
[0006] The present invention provides a coated diaphragm, comprising:
[0007] Basement membrane;
[0008] a coating formed on the base film;
[0009] The coating layer includes a lithium salt, an oxide and a binder; the lithium salt includes a nitrogen-containing lithium salt.
[0010] Preferably, the nitrogen-containing lithium salt includes at least one of lithium nitrate, lithium nitride and lithium amide.
[0011] Preferably, the oxide includes at least one of silicon oxide, aluminum oxide and zirconium oxide.
[0012] Preferably, the binder is polyvinylidene fluoride.
[0013] Preferably, in the coating separator, the mass content of the lithium salt is 5% to 15%, the mass content of the oxide is 75% to 85%, and the mass content of the binder is 5% to 15%.
[0014] Preferably, the coating has a thickness of 5 to 10 μm.
[0015] Preferably, the base film is a polyethylene membrane.
[0016] The present invention also provides a method for preparing the above-mentioned coated diaphragm, comprising the following steps:
[0017] A) mixing a lithium salt, an oxide, a binder and a solvent to obtain a slurry;
[0018] B) The slurry is evenly coated on a base film, and after drying, a coating membrane is obtained.
[0019] Preferably, the solvent is N-methylpyrrolidone;
[0020] The solid content of the slurry is 30% to 45%.
[0021] The present invention also provides a high-voltage lithium metal battery, comprising: a lithium metal negative electrode, a liquid organic electrolyte, a positive electrode and a separator;
[0022] The diaphragm is the coating diaphragm described above or the coating diaphragm prepared by the preparation method described above.
[0023] The present invention provides a coating membrane, comprising: a base membrane; a coating formed on the base membrane; the coating comprises a lithium salt, an oxide and a binder; the lithium salt comprises a nitrogen-containing lithium salt. In the coating membrane provided by the present application, the lithium salt has the function of stabilizing the electrolyte and promoting the formation of a solid SEI layer, the oxide has a mechanical reinforcement effect and a high specific surface area, and the binder is used to improve the wetting performance between the membrane and the electrolyte. The three components can cooperate well with each other, and the main problems that plague lithium metal batteries are solved by inhibiting dendrite growth and promoting SEI stability, thereby improving the overall performance (electrochemical performance) and safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1The SEM images of the lithium metal deposition morphologies in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention are as follows;
[0025] Figure 2 The Coulombic efficiency (CE) diagram of the Li||Cu half-cell in Example 1, Comparative Example 1 and Comparative Example 2 after 25 cycles under constant current charge and discharge conditions;
[0026] Figure 3 It is a long cycle voltage curve of Li||Li symmetric battery in Example 2, Comparative Example 3 and Comparative Example 4 of the present invention;
[0027] Figure 4 Graph showing electrochemical impedance test results of Li||Li symmetric batteries in Example 2, Comparative Example 3 and Comparative Example 4 of the present invention;
[0028] Figure 5 The graphs are the discharge capacity and coulombic efficiency of the lithium metal battery with nickel cobalt manganese oxide (NCM811) as the positive electrode in Example 3, Comparative Example 5 and Comparative Example 6 of the present invention, during 50 cycles under constant current charge and discharge test conditions. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention provides a coated diaphragm, comprising:
[0031] Basement membrane;
[0032] a coating formed on the base film;
[0033] The coating layer includes a lithium salt, an oxide and a binder; the lithium salt includes a nitrogen-containing lithium salt.
[0034] In certain embodiments of the present invention, the nitrogen-containing lithium salt includes at least one of lithium nitrate, lithium nitride and lithium amide; for example, lithium nitrate.
[0035] In certain embodiments of the present invention, the oxide includes at least one of silicon oxide, aluminum oxide and zirconium oxide; for example, silicon oxide.
[0036] In certain embodiments of the present invention, the binder is polyvinylidene fluoride.
[0037] In the coating separator, the mass content of lithium salt is 5% to 15%, the mass content of oxide is 75% to 85%, and the mass content of binder is 5% to 15%.
[0038] Specifically, in the coating separator, the mass content of lithium salt is 10%, the mass content of oxide is 80%, and the mass content of binder is 10%.
[0039] In certain embodiments of the present invention, the raw materials for preparing the coating include lithium salt, oxide, binder and solvent. The solvent may be N-methylpyrrolidone.
[0040] In certain embodiments of the present invention, the coating has a thickness of 5 to 10 μm, such as 8 μm.
[0041] In certain embodiments of the present invention, the base film is a polyethylene diaphragm. The base film has a thickness of 16 to 25 μm, such as 16 μm.
[0042] The present invention also provides a method for preparing the above-mentioned coated diaphragm, comprising the following steps:
[0043] A) mixing a lithium salt, an oxide, a binder and a solvent to obtain a slurry;
[0044] B) The slurry is evenly coated on a base film, and after drying, a coating membrane is obtained.
[0045] In step A):
[0046] In certain embodiments of the present invention, the solvent is N-methylpyrrolidone.
[0047] In certain embodiments of the present invention, the mass content (solid content) of the slurry is 30% to 45%, such as 35%.
[0048] In certain embodiments of the present invention, the mixing time is 20 to 40 minutes, such as 40 minutes.
[0049] In step B):
[0050] In certain embodiments of the present invention, the base film is a polyethylene membrane.
[0051] In certain embodiments of the present invention, the coating method is a knife coating method.
[0052] In certain embodiments of the present invention, the drying temperature is 50-60° C., such as 60° C., and the drying time is 20-25 hours, such as 24 hours. The drying is vacuum drying.
[0053] The present invention also provides a high-voltage lithium metal battery, comprising: a lithium metal negative electrode, a liquid organic electrolyte, a positive electrode and a separator;
[0054] The diaphragm is the coating diaphragm described above or the coating diaphragm prepared by the preparation method described above.
[0055] In certain embodiments of the present invention, the liquid organic electrolyte is a 1 mol / L LiPF6 solution; the solvent includes EC, EMC and FEC, and the volume ratio of EC to EMC is 3:7; and the mass content of FEC in the solvent is 5%.
[0056] In certain embodiments of the present invention, the positive electrode is ternary nickel cobalt manganese oxide (NCM811).
[0057] The high-voltage lithium metal battery is assembled in a glove box, wherein the water oxygen value in the glove box is less than 0.01 ppm.
[0058] In certain embodiments of the present invention, the coated diaphragm can be used to prepare a high-voltage lithium metal battery; the operating voltage of the high-voltage lithium metal battery is 2.6 to 4.3V.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] In the coated diaphragm provided in the present application, the lithium salt has the function of stabilizing the electrolyte and promoting the formation of a solid SEI layer, the oxide has a mechanical reinforcement effect and a high specific surface area, and the binder is used to improve the wetting performance between the diaphragm and the electrolyte. The three components can work well together to solve the main problems that plague lithium metal batteries by inhibiting dendrite growth and promoting SEI stability, thereby improving the overall performance and safety of the battery.
[0061] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.
[0062] In order to further illustrate the present invention, a coating membrane provided by the present invention, its preparation method and application are described in detail below in combination with embodiments, but it should not be understood as limiting the scope of protection of the present invention.
[0063] Example 1
[0064] 1. A method for preparing a coated diaphragm, comprising the following steps:
[0065] 50 mg of lithium nitrate (LiNO3), 400 mg of silicon oxide (SiO2), and 50 mg of polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 1:8:1, and then N-methylpyrrolidone solvent was added to make the solid content in the system 35%, and then stirred and mixed for 40 minutes to obtain a slurry with a certain fluidity; the slurry was coated on a polyethylene diaphragm (thickness of 16 μm) by a doctor blade method, and vacuum dried at 60°C for 24 hours to obtain a coated diaphragm; wherein the thickness of the coating is 8 μm.
[0066] 2. Use the coating membrane prepared in step 1 to assemble a Li||Cu half-cell, with lithium metal as the counter electrode, copper sheet as the working electrode, 1 mol / L LiPF6 solution as the liquid organic electrolyte, and the solvents including EC, EMC and FEC, with a volume ratio of EC to EMC of 3:7; the mass content of FEC in the solvent is 5%. The assembly is carried out in a glove box, in which the water oxygen value is less than 0.01 ppm. Under constant current discharge conditions, the charge is discharged at 0.5 mA cm -2 The deposition experiment was carried out with a high current density, and the morphology of lithium metal deposited on the copper sheet was observed by scanning electron microscopy.
[0067] 3. Use the coated membrane prepared in step 1 to assemble a Li||Cu half-cell, with the copper sheet as the working electrode, the lithium metal as the counter electrode, the liquid organic electrolyte as a 1 mol / L LiPF6 solution, the solvents including EC, EMC and FEC, and the volume ratio of EC to EMC is 3:7; the mass content of FEC in the solvent is 5%; the liquid electrolyte of the control group is a 1 mol / L LiPF6 solution, the solvents including EC and EMC, and the volume ratio of EC to EMC is 3:7. The assembly is carried out in a glove box, in which the water oxygen value is less than 0.01 ppm. A long cycle test is carried out under constant current charge and discharge conditions, with a current density of 0.5 mA cm -2 , the discharge capacity is 1 mAh cm -2 , the charging cut-off voltage is 1V.
[0068] Comparative Example 1
[0069] 1. A method for preparing a coated diaphragm, comprising the following steps:
[0070] 400 mg of silicon oxide (SiO2) and 50 mg of polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 8:1, and then N-methylpyrrolidone solvent was added to make the solid content in the system 35%, and then stirred and mixed for 40 minutes to obtain a slurry with a certain fluidity; the slurry was coated on a polyethylene diaphragm (thickness of 16 μm) by a doctor blade method, and vacuum dried at 60°C for 24 hours to obtain a coated diaphragm; wherein the thickness of the coating is 8 μm.
[0071] 2. Use the coating membrane prepared in step 1 to assemble a Li||Cu half-cell, with lithium metal as the counter electrode, copper sheet as the working electrode, 1 mol / L LiPF6 solution as the liquid organic electrolyte, and the solvents including EC, EMC and FEC, with a volume ratio of EC to EMC of 3:7; the mass content of FEC in the solvent is 5%. The assembly is carried out in a glove box, in which the water oxygen value is less than 0.01 ppm. Under constant current discharge conditions, the charge is discharged at 0.5 mA cm -2The deposition experiment was carried out with a high current density, and the morphology of lithium metal deposited on the copper sheet was observed by scanning electron microscopy.
[0072] 3. Use the coated diaphragm prepared in step 1 to assemble a Li||Cu half-cell, with the copper sheet as the working electrode, the lithium metal as the counter electrode, the liquid organic electrolyte as a 1 mol / L LiPF6 solution, the solvents including EC, EMC and FEC, and the volume ratio of EC to EMC is 3:7; the mass content of FEC in the solvent is 5%; the liquid electrolyte of the control group is a 1 mol / L LiPF6 solution, the solvents including EC and EMC, and the volume ratio of EC to EMC is 3:7. The assembly is carried out in a glove box, in which the water oxygen value is less than 0.01 ppm. The test is carried out under constant current charge and discharge conditions, with a current density of 0.5 mA cm -2 , the discharge capacity is 1 mAh cm -2 , the charging cut-off voltage is 1V.
[0073] Comparative Example 2
[0074] 1. An uncoated commercial polyethylene diaphragm (16 μm thick) was used to assemble a Li||Cu half-cell, with lithium metal as the counter electrode, copper sheet as the working electrode, 1 mol / L LiPF6 solution as the liquid organic electrolyte, and the solvents included EC, EMC and FEC, with a volume ratio of EC to EMC of 3:7; the mass content of FEC in the solvent was 5%. The assembly was carried out in a glove box, in which the water oxygen value was less than 0.01 ppm. Under constant current discharge conditions, the charge was discharged at 0.5 mA cm -2 The deposition experiment was carried out with a high current density, and the morphology of lithium metal deposited on the copper sheet was observed by scanning electron microscopy.
[0075] 3. Use the coated diaphragm prepared in step 1 to assemble a Li||Cu half-cell, with the copper sheet as the working electrode, the lithium metal as the counter electrode, the liquid organic electrolyte as a 1 mol / L LiPF6 solution, the solvents including EC, EMC and FEC, and the volume ratio of EC to EMC is 3:7; the mass content of FEC in the solvent is 5%; the liquid electrolyte of the control group is a 1 mol / L LiPF6 solution, the solvents including EC and EMC, and the volume ratio of EC to EMC is 3:7. The assembly is carried out in a glove box, in which the water oxygen value is less than 0.01 ppm. The test is carried out under constant current charge and discharge conditions, with a current density of 0.5 mA cm -2 , the discharge capacity is 1 mAh cm -2 , the charging cut-off voltage is 1V.
[0076] Figure 1 The SEM images of the lithium metal deposition morphology in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention are shown in FIG. Figure 1It can be seen that the battery using the PE-LiNO3 / SiO2 coated separator in Example 1 shows a denser lithium metal deposition layer. And there are granular substances distributed on the surface, which should be the partial shedding of the separator coating. The battery using the PE-SiO2 coated separator in Comparative Example 1 and the uncoated commercial PE separator in Comparative Example 2 shows uneven lithium growth, containing a large number of dendritic structures. Compared with the traditional PE separator, the improved separator promotes more uniform lithium deposition. This uniform deposition is essential to maintain the structural integrity of the negative electrode and prevent possible battery short circuits.
[0077] Figure 2 The Coulombic efficiency (CE) diagram of the Li||Cu half-cell in Example 1, Comparative Example 1 and Comparative Example 2 after 25 cycles under constant current charge and discharge conditions. 2 The current density and 1 mAh / cm 2 At a capacity of 100,000, we see that the modified PE-LiNO3 / SiO2 maintains a high and consistent Coulombic efficiency (95%) relative to the standard polyethylene (PE) separator in the 1mol / L LiPF6-EC / EMC (3:7)-5wt.% FEC electrolyte system. While the battery using the uncoated commercial PE separator gradually dropped below 90% after 23 cycles, the battery using the PE-SiO2 separator coated with no nitrogen-containing lithium salt also maintained a high and consistent Coulombic efficiency (95%). This shows that although the LiNO3 / SiO2 coating may require a short "running-in" period, it provides a more stable interface for lithium ion transfer and promotes a more uniform SEI layer, which makes the lithium deposition / stripping process more controllable, which is critical to reducing the consumption of lithium metal during cycling.
[0078] Example 2
[0079] 1. A method for preparing a coated diaphragm, comprising the following steps:
[0080] 50 mg of lithium nitrate (LiNO3), 400 mg of silicon oxide (SiO2), and 50 mg of polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 1:8:1, and then N-methylpyrrolidone solvent was added to make the solid content in the system 35%, and then stirred and mixed for 40 minutes to obtain a slurry with a certain fluidity; the slurry was coated on a polyethylene diaphragm (thickness of 16 μm) by a doctor blade method, and vacuum dried at 60°C for 24 hours to obtain a coated diaphragm; wherein the thickness of the coating is 8 μm.
[0081] 2. Use the coated diaphragm prepared in step 1 to assemble a Li||Li half-cell, where lithium metal is the counter electrode and the working electrode, the liquid organic electrolyte is a 1 mol / L LiPF6 solution, and the solvent includes EC, EMC and FEC, with a volume ratio of EC to EMC of 3:7; the mass content of FEC in the solvent is 5%. The assembly is carried out in a glove box, where the water oxygen value is less than 0.01 ppm. A long cycle voltage test is carried out under constant current charge and discharge conditions, with a current density of 0.5 mA cm -2 , the discharge capacity is 1 mAh cm -2 , the charging cut-off voltage is 1V.
[0082] 3. The coated diaphragm prepared in step 1 is used to assemble a Li||Li symmetric battery, where lithium metal is the counter electrode and the working electrode respectively, the liquid organic electrolyte is a 1 mol / L LiPF6 solution, and the solvent includes EC, EMC and FEC, and the volume ratio of EC to EMC is 3:7; in the solvent, the mass content of FEC is 5%. The assembly is carried out in a glove box, in which the water oxygen value is less than 0.01 ppm. The impedance test is carried out using a CHI760E electrochemical workstation, and the test range is 100000Hz-0.1Hz.
[0083] Comparative Example 3
[0084] 1. A method for preparing a coated diaphragm, comprising the following steps:
[0085] 400 mg of silicon oxide (SiO2) and 50 mg of polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 8:1, and then N-methylpyrrolidone solvent was added to make the solid content in the system 35%, and then stirred and mixed for 40 minutes to obtain a slurry with a certain fluidity; the slurry was coated on a polyethylene diaphragm (thickness of 16 μm) by a doctor blade method, and vacuum dried at 60°C for 24 hours to obtain a coated diaphragm; wherein the thickness of the coating is 8 μm.
[0086] 2. Use the coated diaphragm prepared in step 1 to assemble a Li||Li half-cell, where lithium metal is the counter electrode and the working electrode, the liquid organic electrolyte is a 1 mol / L LiPF6 solution, and the solvent includes EC, EMC and FEC, with a volume ratio of EC to EMC of 3:7; the mass content of FEC in the solvent is 5%. The assembly is carried out in a glove box, where the water oxygen value is less than 0.01 ppm. A long cycle voltage test is carried out under constant current charge and discharge conditions, with a current density of 0.5 mA cm -2 , the discharge capacity is 1 mAh cm -2 , the charging cut-off voltage is 1V.
[0087] 3. The coated diaphragm prepared in step 1 is used to assemble a Li||Li symmetric battery, where lithium metal is the counter electrode and the working electrode respectively, the liquid organic electrolyte is a 1 mol / L LiPF6 solution, and the solvent includes EC, EMC and FEC, and the volume ratio of EC to EMC is 3:7; in the solvent, the mass content of FEC is 5%. The assembly is carried out in a glove box, in which the water oxygen value is less than 0.01 ppm. The impedance test is carried out using a CHI760E electrochemical workstation, and the test range is 100000Hz-0.1Hz.
[0088] Comparative Example 4
[0089] 1. An uncoated commercial polyethylene diaphragm (16 μm thick) was used to assemble a Li||Li half-cell. Lithium metal was used as the counter electrode and the working electrode, respectively. The liquid organic electrolyte was a 1 mol / L LiPF6 solution. The solvents included EC, EMC and FEC. The volume ratio of EC to EMC was 3:7. The mass content of FEC in the solvent was 5%. The assembly was carried out in a glove box, where the water oxygen value was less than 0.01 ppm. A long cycle voltage test was carried out under constant current charge and discharge conditions with a current density of 0.5 mA cm -2 , the discharge capacity is 1 mAh cm -2 , the charging cut-off voltage is 1V.
[0090] 2. The coated diaphragm prepared in step 1 is used to assemble a Li||Li symmetric battery, where lithium metal is the counter electrode and the working electrode respectively, the liquid organic electrolyte is a 1 mol / L LiPF6 solution, and the solvent includes EC, EMC and FEC, and the volume ratio of EC to EMC is 3:7; in the solvent, the mass content of FEC is 5%. The assembly is carried out in a glove box, in which the water oxygen value is less than 0.01 ppm. The impedance test is carried out using a CHI760E electrochemical workstation, and the test range is 100000Hz-0.1Hz.
[0091] Figure 3It is a long cycle voltage curve of Li||Li symmetric battery in Example 2, Comparative Example 3 and Comparative Example 4 of the present invention. It can be seen that in the initial stage, the polarization of the three membrane systems is small, and the overpotential is about 50mV. However, as the cycle time increases, the time-voltage curve polarization of the PE-SiO2 / LiNO3 membrane system is the smallest, and the overpotential is only 50mV with a steady downward trend. The polarization of PE-SiO2 and uncoated PE membranes begins to increase significantly, especially the PE-SiO2 membrane, whose overpotential increases sharply to 300mV after 150 cycles. This shows that the modified PE-SiO2 / LiNO3 membrane has the following advantages: 1) Enhanced ion conduction: It promotes excellent ion mobility and ensures that lithium ions can move freely and evenly in the battery, thereby reducing the possibility of concentration gradients that lead to polarization; 2) Optimized electrode interface: The coating may form a more compatible and conductive interface with lithium metal, enhance the charge transfer kinetics in the electrochemical reaction and reduce the overpotential; 3) Uniform SEI formation: The PE-SiO2 / LiNO3 membrane promotes a stable electrochemical environment, which is conducive to the formation of a uniform solid electrolyte interface phase on the lithium negative electrode. The uniform SEI acts as a protective layer, keeping the lithium ion flux consistent and mitigating the formation of dendrites; 4) Reduced electrolyte decomposition: A stable voltage curve generally corresponds to reduced parasitic reactions between the electrolyte and the electrode, such as those side reactions that lead to electrolyte decomposition.
[0092] In summary, the modified PE-SiO2 / LiNO3 separator significantly improves the stability and life of Li||Li batteries by affecting the battery internal resistance and ion transport pathways. This is achieved by enabling efficient lithium deposition and stripping, which is critical for high-performance lithium metal batteries as they are expected to cycle stably for a long time with minimal side reactions.
[0093] Figure 4 The electrochemical impedance test results of the Li||Li symmetric battery in Example 2, Comparative Example 3 and Comparative Example 4 of the present invention are shown in FIG. Figure 4 It can be seen that the charge transfer resistance of the modified PE-SiO2 / LiNO3 separator is significantly reduced, as evidenced by the reduction in the diameter of the semicircle in the Nyquist plot, which is only less than 60Ω, while the PE-SiO2 and uncoated PE separators are 85-90Ω and 75-80Ω, respectively. A more compact semicircle generally indicates a reduction in the interfacial resistance between the electrolyte and the electrode, and a lower charge transfer resistance, which can be explained by a stronger conductive interface for lithium ions. This increase in conductivity may be due to the surface properties of the modified separator, which promotes better electrode wettability and more efficient lithium ion transfer. The dip in the low-frequency region indicates that the modified separator has no significant hindering effect on lithium ion diffusion. Therefore, the overall impedance is reduced, which is also beneficial for high-power applications that require fast charge and discharge cycles.
[0094] Example 3
[0095] 1. A method for preparing a coated diaphragm, comprising the following steps:
[0096] 50 mg of lithium nitrate (LiNO3), 400 mg of silicon oxide (SiO2), and 50 mg of polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 1:8:1, and then N-methylpyrrolidone solvent was added to make the solid content in the system 35%, and then stirred and mixed for 40 minutes to obtain a slurry with a certain fluidity; the slurry was coated on a polyethylene diaphragm (thickness of 16 μm) by a doctor blade method, and vacuum dried at 60°C for 24 hours to obtain a coated diaphragm; wherein the thickness of the coating is 8 μm.
[0097] 2. Use the coated diaphragm prepared in step 1 to assemble a high-voltage lithium metal battery, with lithium nickel cobalt manganese oxide (NCM811) as the positive electrode, lithium metal as the negative electrode, a liquid organic electrolyte of 1 mol / L LiPF6 solution, and solvents including EC, EMC and FEC, with a volume ratio of EC to EMC of 3:7; in the solvent, the mass content of FEC is 5%. The assembly is carried out in a glove box, in which the water oxygen value is less than 0.01 ppm. The test is carried out under constant current charge and discharge conditions. After 3 cycles of activation, 0.5C charge and 0.5C discharge cycles are performed, and the voltage range is 2.6V-4.3V.
[0098] Comparative Example 5
[0099] 1. A method for preparing a coated diaphragm, comprising the following steps:
[0100] 400 mg of silicon oxide (SiO2) and 50 mg of polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 8:1, and then N-methylpyrrolidone solvent was added to make the solid content in the system 35%, and then stirred and mixed for 40 minutes to obtain a slurry with a certain fluidity; the slurry was coated on a polyethylene diaphragm (thickness of 16 μm) by a doctor blade method, and vacuum dried at 60°C for 24 hours to obtain a coated diaphragm; wherein the thickness of the coating is 8 μm.
[0101] 2. Use the coated diaphragm prepared in step 1 to assemble a high-voltage lithium metal battery, with lithium nickel cobalt manganese oxide (NCM811) as the positive electrode, lithium metal as the negative electrode, a liquid organic electrolyte of 1 mol / L LiPF6 solution, and solvents including EC, EMC and FEC, with a volume ratio of EC to EMC of 3:7; in the solvent, the mass content of FEC is 5%. The assembly is carried out in a glove box, in which the water oxygen value is less than 0.01 ppm. The test is carried out under constant current charge and discharge conditions. After 3 cycles of activation, 0.5C charge and 0.5C discharge cycles are performed, and the voltage range is 2.6V-4.3V.
[0102] Comparative Example 6
[0103] 1. A non-coated commercial polyethylene diaphragm (16 μm thick) was used to assemble a high-voltage lithium metal battery. Nickel cobalt manganese oxide (NCM811) was used as the positive electrode, lithium metal was used as the negative electrode, the liquid organic electrolyte was a 1 mol / L LiPF6 solution, and the solvent included EC, EMC and FEC. The volume ratio of EC to EMC was 3:7. In the solvent, the mass content of FEC was 5%. The assembly was carried out in a glove box, in which the water oxygen value was less than 0.01 ppm. The test was carried out under constant current charge and discharge conditions. After 3 cycles of activation, 0.5C charge and 0.5C discharge cycles were performed, and the voltage range was 2.6V-4.3V.
[0104] Figure 5 The discharge capacity and coulomb efficiency diagram of the lithium metal battery with nickel cobalt manganese oxide (NCM811) as the positive electrode in Example 3, Comparative Example 5 and Comparative Example 6 of the present invention in 50 cycles under constant current charge and discharge test conditions are shown. The results show that when charged to a high voltage of 4.3V, the lithium metal battery using the PE-LiNO3 / SiO2 diaphragm in Example 3 maintains a relatively high discharge capacity of about 200mAh / g in 50 cycles, and the capacity retention rate is greater than 95%; while the lithium metal battery using the nitride-free PE-SiO2 diaphragm in Comparative Example 5 and the commercial PE diaphragm in Comparative Example 6 begins to show a sharp capacity decay when the cycle reaches 30 cycles, and is less than 100mAh / g after 50 cycles, and the capacity retention rate is less than 50%. This shows that the synergistic effect of the LiNO3 / SiO2 combination is particularly effective in maintaining a stable electrochemical interface in the battery. A stable interface can minimize the propensity of lithium to participate in side reactions, which can deplete the available lithium in the battery and lead to capacity fade. Even with matched high-voltage, high-capacity cathode materials, the consistently high coulombic efficiency indicates low lithium loss, indicating that the SEI layer is effective and side reactions are minimized.
[0105] It can be seen from the above-mentioned embodiments that the PE separator with LiNO3 / SiO2 coating can obtain high-performance high-voltage lithium metal batteries.
[0106] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.
Claims
1. A coated diaphragm, comprising: Basement membrane; a coating formed on the base film; The coating layer includes a lithium salt, an oxide and a binder; the lithium salt includes a nitrogen-containing lithium salt.
2. The coated diaphragm according to claim 1, characterized in that The nitrogen-containing lithium salt includes at least one of lithium nitrate, lithium nitride and lithium amide.
3. The coated diaphragm according to claim 1, characterized in that The oxide includes at least one of silicon oxide, aluminum oxide, and zirconium oxide.
4. The coated diaphragm according to claim 1, characterized in that The binder is polyvinylidene fluoride.
5. The coated diaphragm according to claim 1, characterized in that In the coating separator, the mass content of lithium salt is 5% to 15%, the mass content of oxide is 75% to 85%, and the mass content of binder is 5% to 15%.
6. The coated diaphragm according to claim 1, characterized in that The coating has a thickness of 5 to 10 μm.
7. The coated diaphragm according to claim 1, characterized in that The base film is a polyethylene diaphragm.
8. A method for preparing the coated membrane according to any one of claims 1 to 7, comprising the following steps: A) mixing a lithium salt, an oxide, a binder and a solvent to obtain a slurry; B) The slurry is evenly coated on a base film, and after drying, a coating membrane is obtained.
9. The preparation method according to claim 8, characterized in that: The solvent is N-methylpyrrolidone; The solid content of the slurry is 30% to 45%.
10. A high voltage lithium metal battery comprising: Lithium metal anode, liquid organic electrolyte, cathode and separator; The diaphragm is the coated diaphragm according to any one of claims 1 to 7 or the coated diaphragm prepared by the preparation method according to claims 8 to 9.
Citation Information
Patent Citations
Composite separator, lithium battery and preparation methods thereof
CN106876633A
Separator and lithium-sulfur battery comprising same
CN109565018A
Ceramic coating on separator for batteries
CN112655111A
Preparation method of pole piece, positive pole piece and lithium ion battery
CN115714164A
Lithium secondary battery
KR1020180043183A
Cited By
Preparation method of high-heat-safety lithium battery diaphragm based on magnesium-based whiskers
CN121584149A